How well is hypertension managed in the community? A population-based survey in a Brazilian city O manejo da hipertensão arterial sistêmica na comunidade:estudo de base populacional em uma cidade brasileira - Roberto X. Piccini; Cesar G. Victora (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 1997)
There is usually little information available on how well hypertensive individuals are managed at the community level. This survey measured the frequency of hypertension in a medium-sized Brazilian city by studying a cluster sample of 1657 adults aged 20-69 years. The 328 hypertensives (19.8%) answered a questionnaire on the knowledge and management of their condition. Two-thirds were aware of their status and more than half were on antihypertensive medication, but only one-third had their blood pressure under control. Physicians failed to advise a large proportion of their patients about the need to lose weight, take exercise, and quit smoking. Although laboratory tests were carried out in most patients, fundoscopy and chest X-rays were performed in fewer than 50%. Continued care by the same physician was the only factor significantly associated with compensated high blood pressure (relative risk for not having continued care = 1.35; 95% CI = 1.02-1.71). High levels of absenteeism, reduction of the work load, and early retirement were found among the individuals with high blood pressure. Há poucas informações disponíveis a respeito do manejo de pacientes hipertensos na comunidade. Esse estudo mede a freqüência de hipertensão em uma cidade de médio porte do Brasil ao estudar uma amostra aleatória de 1.657 adultos com idade entre 20 e 69 anos. Os 328 hipertensos (19,8%) encontrados foram submetidos a um questionário que investigava o conhecimento a respeito de sua condição e dados do manejo deste problema. Dois terços deles sabiam ser hipertensos, mais da metade usava medicação para hipertensão, mas apenas um terço apresentava cifras tensionais controladas. Os médicos não recomendaram, para muitos dos seus pacientes, realizarem exercícios físicos, abandonar o tabagismo e reduzirem o peso corporal. Embora exames laboratoriais tenham sido realizados em muitos pacientes, exame de fundo de olho e Rx de tórax foram feitos em menos de 50%. Cuidado médico continuado pelo mesmo médico foi o único fator significativamente associado com cifras tensionais controladas (risco relativo para não ter cuidado médico continuado = 1,35, com intervalo de confiança de 95% de 1,02 a 1,71). Níveis elevados de absenteismo, redução da carga de trabalho e aposentadoria precoce foram revelados entre os hipertensos.